2018
DOI: 10.1016/j.jdermsci.2017.10.012
|View full text |Cite
|
Sign up to set email alerts
|

TRPA1 channel participates in tacrolimus-induced pruritus in a chronic contact hypersensitivity murine model

Abstract: Letter to the EditorTRPA1 channel participates in tacrolimus-induced pruritus in a chronic contact hypersensitivity murine model Keywords Tacrolimus TRPA1 channel Atopic dermatitis Contact hypersensitivity

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 10 publications
0
7
1
Order By: Relevance
“…Interestingly, on day 16, MCE ME vehicle ameliorated the DNCB-induced skin similar to the oil-free group ( P >0.05), and both of them were greater than the commercial ointment ( P <0.05), which indicated that the vehicle containing MCE could decrease AD symptoms and the lower concentration of surfactant and co-surfactant in MCE ME did not irritate the AD-like skin. The commercial ointment irritates skin, resulting in erythema, dryness, and itching in AD patients 22. Moreover, we observed that it is difficult for the commercial ointment with sticky ointment to spread out on the impaired skin during the treatment.…”
Section: Resultsmentioning
confidence: 84%
See 1 more Smart Citation
“…Interestingly, on day 16, MCE ME vehicle ameliorated the DNCB-induced skin similar to the oil-free group ( P >0.05), and both of them were greater than the commercial ointment ( P <0.05), which indicated that the vehicle containing MCE could decrease AD symptoms and the lower concentration of surfactant and co-surfactant in MCE ME did not irritate the AD-like skin. The commercial ointment irritates skin, resulting in erythema, dryness, and itching in AD patients 22. Moreover, we observed that it is difficult for the commercial ointment with sticky ointment to spread out on the impaired skin during the treatment.…”
Section: Resultsmentioning
confidence: 84%
“…The transient irritations mainly associated with the drug characteristic of TCIs 19. TCIs can activate the transient receptor potential A1 (TRPA1) channel followed by SP release, which induces the initial side effects of burning and itching during the therapy with FK506,2022 and itch-triggered scratching immediately leads to symptom exacerbation, and pruritus–scratch–pruritus easily turns into a vicious circle. These irritations of FK506 in AD patients often lead to treatment discontinuation.…”
Section: Introductionmentioning
confidence: 99%
“…FK506-induced pancreatitis-related pain was attenuated by an antagonist of TRPV1, but not by voltage-gated Ca 2+ channels in mice [44]. FK506 enhanced TRPA1 expression in a murine model of oxazolone-induced chronic hypersensitivity and FK506-induced scratching behaviors were reduced by a TRPA1 antagonist [57]. In this study, we found that local injection of FK506 induced acute licking or biting behaviors through TRPA1 activation (Fig.…”
Section: Discussionmentioning
confidence: 56%
“…TRPA1 involvement can also occur downstream, particularly in models which have a defined receptor target associated with itch, e.g., using SLIGRL to activate MrgprC11 [41], chloroquine to activate Mrgpra3/X1 [42], serotonin to activate HTR7 [43], TSLP to activate the TSLP receptor [44], and IL31 to activate the IL31 receptor [45]. These diverse mediators converge on common pathways as modulating G protein-coupled receptors, and TRPA1 has been shown to be essential in these pathways [46,47,48,49].…”
Section: Symptomatic Therapy—antipruritic Potentialmentioning
confidence: 99%
“…Atopic dermatitis is a burdensome allergic disease with therapy-resistant chronic itch as a hallmark. In an oxazolone-based animal model of chronic dermatitis, TRPA1 inhibition could reduce scratching [47]. Scratching induced by IL-13 or IL-31 in atopic dermatitis models was reduced in TRPA1-deficient mice or by TRPA1 inhibition [45,50].…”
Section: Symptomatic Therapy—antipruritic Potentialmentioning
confidence: 99%